Cold Fission. - Moore, Samuel K.
Global Technologies is working on a nuclear voltaic cell consisting basically of a semiconductor and an amount of radioactive material. By replacing solid semiconductors with molten selenium and molten sulfur, GT's nuclear battery could run on much more powerful radiation than a beta cell and therefore generate more electricity
Keywords: Global Technologies; Alpha radiation; Beta radiation; Liquid semiconductors; Nuclear battery; Nuclear voltaic cell; Radioactive material